Король: Вечный монарх. Сквозь время - Ким Ынсук (Лучшие дорамы, 2022)
Экземпляры: ЦБ (20230508) / Инвентарный номер: 57404 / Цена: 462.33 / Сис.шифр: 84(4/8) / Авт.знак: К 40 / ГРНТИ: 17.82.31 / ББК: 84(5Кор)-44